2004
DOI: 10.1007/s00221-004-2004-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the thumb a fifth finger? A study of digit interaction during force production tasks

Abstract: We studied indices of digit interaction in single-and multi-digit maximal voluntary contraction (MVC) tests when the thumb acted either in parallel or in opposition to the fingers. The peak force produced by the thumb was much higher when the thumb acted in opposition to the fingers and its share of the total force in the five-digit MVC test increased dramatically. The fingers showed relatively similar peak forces and unchanged sharing patterns in the four-finger MVC task when the thumb acted in parallel and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 44 publications
5
27
0
Order By: Relevance
“…However, during the multidigit tasks, total enslavement was similar to that when the thumb acted in parallel (ϳ15% MVC; see Fig. 5 in Olafsdottir et al 2005). Furthermore, the summed force deficits in the present study were also similar to the data for the thumb acting in parallel (ϳ30% MVC here; see Fig.…”
Section: Single-digit Performancesupporting
confidence: 83%
See 3 more Smart Citations
“…However, during the multidigit tasks, total enslavement was similar to that when the thumb acted in parallel (ϳ15% MVC; see Fig. 5 in Olafsdottir et al 2005). Furthermore, the summed force deficits in the present study were also similar to the data for the thumb acting in parallel (ϳ30% MVC here; see Fig.…”
Section: Single-digit Performancesupporting
confidence: 83%
“…Neural interactions involving drive to the long flexors of the fingers and thumb have been reported (Hockensmith et al 2005;Kilbreath and Gandevia 1994;Yu et al 2007). During a pressing task with the fingers and thumb, Olafsdottir et al (2005) reported that the degree of thumb enslavement depended on its position. There was more enslavement when the thumb was positioned opposite the fingers than when it acted in parallel with the fingers.…”
Section: Single-digit Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Shim et al 2004b), and involvement of the thumb (Olatsdottir et al 2005). We would like to note, however, that at least one study reported high indices of moment-stabilizing synergies during more natural grasping tasks (Shim et al 2004a).…”
Section: Concluding Commentsmentioning
confidence: 89%